(untitled) (Baghdad Science Journal, 2024)
The aim of this study was to measure the levels of malondialdehyde (MDA), peroxynitrite (PN), homocysteine (HCY), and uric acid (UA) in acute myeloid leukemic patients (AML) (before and after taking chemotherapy) and compare results with a healthy control group. The present study includes 120 age ranged 18-70 years old suffered from AML as well as 40 healthy group. Subjects were collected from patients and a control group at Erbil’s Nanakali Hospital, they were classified into four groups: Group 1 (G1) which includes 40 healthy subjects, Group 2 (G2) includes 40 AML patients before taking chemotherapy (newly diagnosed cases), Group 3 (G3) includes 40 AML patients after taking chemotherapy (one cycle) and Group 4 (G4) includes 40 AML patients after taking chemotherapy (more than one cycle). The results have shown a high significantly increased in levels of (MDA and UA), and significantly increased in PN in all patient groups (G1, G2, and G3) when compared to (G1). While homocysteine was a high significantly increased in (G2) when compared to (G1), and high significantly decreased in (G3 and G4) as compared to (G1). Additionally, the correlation analysis has shown that there was a significant positive correlation between malondialdehyde and peroxynitrite (r=0.4638), malondialdehyde and homocysteine (r=0.4752), and malondialdehyde with uric acid (r=0.3621). A high area under the curve of our data suggests that the determination of these parameters could be helpful to detect AML